If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 + -4x = 5 + -7x Solving 23 + -4x = 5 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 23 + -4x + 7x = 5 + -7x + 7x Combine like terms: -4x + 7x = 3x 23 + 3x = 5 + -7x + 7x Combine like terms: -7x + 7x = 0 23 + 3x = 5 + 0 23 + 3x = 5 Add '-23' to each side of the equation. 23 + -23 + 3x = 5 + -23 Combine like terms: 23 + -23 = 0 0 + 3x = 5 + -23 3x = 5 + -23 Combine like terms: 5 + -23 = -18 3x = -18 Divide each side by '3'. x = -6 Simplifying x = -6
| X+2-X+3= | | 64x+3=12x-3 | | 22x+1/2+50-600+1000=74 | | X-19x-20= | | X-1+Y+Y+Y= | | -24x+6y=18 | | 4w^2+20w+25=225 | | 7Y-4+4-2Y= | | 3(x+2)(x-2)= | | 7x^21+14x=0 | | 23280.55=x+(x*.0825) | | 5(x-6)=3x-18+3x | | -7/3-2/3 | | 5x-14y=22 | | x-2/2=4 | | -5x-10y=-15 | | 3x(2x-7)=12 | | -8/3(-4/7) | | x+6=2+x+4 | | 2x-4-6x=3x-7 | | h(t)=-12t^2+80t | | 36=4(y-1) | | 5(x-100)=2(x-100) | | (y-8)-(y+6)= | | 4(5b-7)=10b+2 | | 5x+7y=-8 | | x+x+6=46 | | 13x+3(x+11)=8x-7 | | 6a+-92=2a | | g-2/5g=3 | | 1/3=k-4 | | 2(3x-6)=x+4+5x |